2007
DOI: 10.1074/jbc.m610707200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Heparan Sulfate 2-O-Sulfotransferase in Chick Limb Bud Patterning and Development

Abstract: Although growth factors and morphogens are required for limb bud development and patterning, it is unclear how their signaling and distribution are regulated. Heparan sulfate proteoglycans, which are ubiquitous on the cell surface and in the extracellular matrix including basement membranes, are important regulators of such growth factor signaling and distribution (9 -11). For example, chicken syndecan-3 is expressed throughout the distal mesenchymal cells and plays a role in limb bud outgrowth by controlling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 74 publications
(78 reference statements)
1
19
0
Order By: Relevance
“…This hypothesis is noteworthy as the majority of agrin morphant phenotypes are similar to fgf mutant or morphant phenotypes, which include disrupted formation of the MHB, otic vesicle, tail, and eye (Kim et al, 2007). Since Fgfs require heparin binding for activity (Yayon et al, 1991;Kan et al, 1993), Fgf expression and signaling is dependent on heparan sulfate sulfation/structure (Kobayashi et al, 2007), and agrin is a HSPG (Denzer et al, 1995;Tsen et al, 1995), these data are consistent with a mechanism whereby agrin regulation of Fgf signaling contributes to retinal development. Furthermore, previously we have shown that agrin modulates Fgf2-mediated RGC axon outgrowth by a mechanism that includes potentiation of MAP kinase phosphorylation in RGCs (Kim et al, 2003).…”
Section: Agrin Morphant Phenotypes May Occur Due To Disrupted Fgf Sigsupporting
confidence: 55%
“…This hypothesis is noteworthy as the majority of agrin morphant phenotypes are similar to fgf mutant or morphant phenotypes, which include disrupted formation of the MHB, otic vesicle, tail, and eye (Kim et al, 2007). Since Fgfs require heparin binding for activity (Yayon et al, 1991;Kan et al, 1993), Fgf expression and signaling is dependent on heparan sulfate sulfation/structure (Kobayashi et al, 2007), and agrin is a HSPG (Denzer et al, 1995;Tsen et al, 1995), these data are consistent with a mechanism whereby agrin regulation of Fgf signaling contributes to retinal development. Furthermore, previously we have shown that agrin modulates Fgf2-mediated RGC axon outgrowth by a mechanism that includes potentiation of MAP kinase phosphorylation in RGCs (Kim et al, 2003).…”
Section: Agrin Morphant Phenotypes May Occur Due To Disrupted Fgf Sigsupporting
confidence: 55%
“…Therefore, it can connect extra-and intracellular signaling events, which regulate development, immune response, anticoagulation, stem cell fate, and tissue morphogenesis. 4,22,23 Therefore, sugar chains like heparan sulfate can successfully reproduce a stem cell niche and have therefore applications in regenerative medicine. Their application as biomaterials requires a close structural control and the need for large-scale synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…They observed renal agenesis as well as eye and skeletal defects. Recently, it was found that 2OST is essential for FGF signaling required in chick limb bud outgrowth and development [39]. …”
Section: Discussionmentioning
confidence: 99%